Pengaruh Jarak Usia Kelahiran dengan Terjadinya Respon Sibling pada Anak Usia 2-4 Tahun - Noviari Triwijayanti; Levi Tina Sari (STIKes Patria Husada Blitar, 2014)
Sibling response is competition in order to get love and care of one or both parents. The birth distance of a child is an important factor in the emergence of sibling response, because short spacing births of child tends to rise sibling negatif response. The puspose of this study was to identify the effect of age distance of birth to the sibling responses in 2-4 years old children. Method : Research design wascross sectional. Research sample was 26 respondent at BPS Mutiah Bendo Village Ponggok District of Blitar, at July 9th to July 20, 2012, its choosed with tota sampling. Data collected by using a structured interview and observation statements in the questionnaire. Analysis using T-Test, with ≤0.05 significant level. Result :The result showed that most of the respondents gave negativ responses for the short spacing of births, with p = 0,023. Discussion : There was an effect of space of birth with the sibling responses in children age of 2 – 4 years by 61,5% of the respondents, and sibling negative response in children age of 2 – 4 years by 71,4 % of the respondents.